A byproduct of uvaia (Eugenia pyriformis) processing as a natural source for coloring sugar hard‐panning confections. (12th September 2019) - de Avelar, Matheus H. M.; da Silva, Lidiane B.; de Azevedo, Fábio B.; Efraim, Priscilla
Abstract: Due to the increased demand for healthier confectionery products and the great importance of finding environmentally appropriate destinations for fruit processing byproducts, this study evaluated the performance of a Brazilian fruit (uvaia, Eugenia pyriformis ) byproduct in coloring sugar hard‐panning confections compared to synthetic caramel color and a natural fruit/plant‐based concentrate. The obtained products were characterized according to their sensory acceptance, instrumental texture and color, water activity, moisture content, glass transition temperature, and sorption isotherm. A strong influence of the coloring agents was observed on the coatings' physical and chemical parameters. Comparatively, the uvaia byproduct induced a significant increase in the hardness and glass transition temperature of the confection, which may result in better stability concerning the maintenance of crunchiness. A sensory preference for naturally colored confections compared to a synthetically colored confection was observed. The uvaia byproduct presents technological potential as a sustainable coloring agent with low cost for confections. Practical applications: Panned products account for a considerable portion of the total confectionery volume consumed worldwide. The inclusion of fruit processing byproducts in panned confections, specifically for the uvaia byproduct, is presented as a viable alternative for the natural coloring of a confectionery using a sustainable and low‐cost ingredient. The methodology developed in this study has the potential to replace the conventional coloring additive for hard sugar‐panned confectionery products, and it may be applicable in several types of confectionery products. The use of fruit byproducts with ability to impact color to the coating of panned confections may allow the removal of synthetic color additives, reducing the consumption of artificially colored products, and the occurrence of adverse reactions in consumer health.